A Multi-Stage Model of Adoption of Online Buying in India. Issue 2 (15th March 2018) - Rajaretnam, Jeyachandran; N. Sheth, Jagdish
ABSTRACT: An understanding of adoption of online buying is important in order to develop the right strategies to promote ecommerce in emerging markets. The article reviews various models of adoption in the Internet and technology areas and presents a multi-stage model of adoption of online buying. The model was tested with an empirical study which supports the stages of the model proposed. Further, the model explains certain situations in which an Internet user may skip a stage in the adoption process. The skipping of a stage is also supported by the findings. The article also explores various antecedents, motivating factors, and demographic characteristics which propel an Internet user to move from one stage to the next in the adoption process. The findings confirm that trust plays an important role in one of the stages of the adoption process. Further, online buyers were found to be more affluent than offline buyers.